PENGEMBANGAN MEDIA PEMBEJARAN BONEKA KAUS KAKI UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS II SEKOLAH DASAR - Erwin Putera Permana (Universitas Muhammadiyah Surakarta, 2015)
The purpose of this study are: (1) to produce instructional media sock puppets which are practical,attractive, effective and efficient in improving speaking skills of elementary school students, (2)to determine the steps of making media sock puppets to improve speaking skills elementary schoolstudents, and (3) to test the feasibility of instructional media products which include practicality, theattractiveness, effectiveness and efficiency of the product. This study uses a model of the development of amodified Borg Gall. The steps of this research, namely (1) Preliminary Study, (2) Planning, (3) DesignProducts, (4) Product Validation, (5) Trial Product, and (6) End Product. The practical implications ofthis research is to develop the basic capabilities of cognitive, affective and psychomotor learning funthrough the media. The use of storytelling with a sock puppet media proved to meet these objectives.